THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) AND NUMBERED HEAD TOGETHER (NHT) TOWARD MATHEMATICS LEARNING OUTCOME - Muhammad Fajar Wilda Chadhiq; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Learning that tends dominated by teachers leads students are less active in the following study. Students only passively accept the teaching of teachers so that students have difficulty in understanding the material. It is thought to be one of the factors that led to lower students’ mathematics learning outcomes. This research is intended to find out the effectiveness of the cooperative learning model type of student teams achievement division (STAD) and numbered head together (NHT) toward mathematics learning outcome of the VIII grade students of SMP Negeri 2 sewon Kabupaten bantul in the odd semester of academic year of 2016/2017. This study uses a posttest-only control design. There is three class in the population of this study, samples were taken from two classes with random sampling techniques to the class. Data collection was conducted with the test model. The instrument used questions related to the subject of algebra. Before analyzing data, there is a prerequisite test that consists of a normality test and a homogeneity test to do. The data analysis using t-test two parties and one party t-test.  The results of a study on the significant level of 5% and dk = 53 indicating that there is a significant difference between the results of learning mathematics using cooperative learning model STAD with the use of models NHT type of cooperative learning. This is indicated by the value and  which mean  and STAD cooperative learning model is more effective than the cooperative learning model NHT type, against the mathematic learning student's results. This is indicated by the value  and  which mean.